133k views
0 votes
What is 3(x-4)+6=5(x-1)+1 equal to?

User Saalon
by
4.8k points

2 Answers

3 votes

Hello there!

3(x+4)+6=5(x-1)+1

Use the Disrtributive Property:

3x+12+6=5x-5+1

3x+18=5x-4

3x-5x=-4-18

-2x=-22

Divide both sides by -2 to isolate x:

x=11

Hope this helps you!

~Just a joyful teen


SilentNature :)

User Vajda
by
4.4k points
4 votes

____________________________________________________

Answer:

x = -1

____________________________________________________

Explanation:

Solve for x in the equation: 3(x-4)+6=5(x-1)+1


3(x-4)+6=5(x-1)+1\\\\\text{Distribute the 3}\\\\3x - 12 + 6 =5(x-1)+1\\\\\text{Distribute the 5}\\\\3x - 12 + 6 =5x-5+1\\\\3x - 12 + 6 =5x-4\\\\3x - 6 =5x-4\\\\\text{Subtract 5x to both sides}\\\\-2x-6=-4\\\\\text{Add 6 to both sides}\\\\-2x=2\\\\\text{Divide by -2}\\\\x=-1

____________________________________________________

User Ben Sandofsky
by
5.8k points